Method of incorporation of natural antioxidant from cinnamon leaf oil as an antioxidant into surgical and examination gloves - Abira, S.; Gunaratne, R.D.; Paranagama, P.A.; De Silva, K.R.D (My University, 2017)
Attached

The number of surgical/examination gloves used globally in health care has increased dramatically and allergic contact dermatitis develops on the hands after exposure to latex examination gloves. Surgical glove chemicals are the most frequent causes of occupational allergic contact dermatitis in health care workers as a result of frequent glove use. Contact allergy to surgical gloves is also caused by antioxidants that are used to prevent rubber degradation. A number of plant secondary metabolites act as scavengers of free radical species and so have been classified as antioxidants. The present study aims to describe the potential of cinnamon leaf oil as an alternative natural antioxidant in the glove industry. Cinnamon zeylanicum is an endemic plant in Sri Lanka and the essential oils from bark and leaf are heavily used in perfume and food industries. In the present study cinnamon leaf oils were extracted using Clevenger apparatus and the percentage yield of the essential oil was 3.2 %. The quality of the essential oil was compared with a commercial sample using Gas chromatography. It was confirmed that both samples contained 78-80% eugenol. The radical scavenging activity of cinnamon leaf oil has been evaluated using 2, 2-diphenyl-1picryl-hydrazyl-hydrate (DPPH) assay and BHT was used as the positive control. The results revealed that 100 % radical scavenging activity was shown at 10 g/mL concentration of the essential oil. The cinnamon leaf oil has the highest antioxidant activity (IC50 = 8.33 g/mL) which is three times less than the synthetic antioxidant BHT (24.09 g/mL). Lower IC50 value indicates higher antioxidant activity. Therefore it is confirmed that cinnamon leaf oil can be used as the antioxidant to develop surgical/examination gloves. Future studies will be concentrated to investigate a suitable percentage of the stabilizer and the emulsifier in order to prepare a homogeneous solution of the essential oil to be used in the surgical/examination glove manufacturing process.
Keywords: antioxidant, surgical/examination glove, essential oil